Perlindungan Hukum Terhadap Anak Akibat Dari Perkawinan WNI Dengan WNA Di Kecamatan Cisarua Kabupaten Bogor - Agung Wiraguna; Kholil Nawawi (CV. ITTC INDONESIA, 2024)
Country marriages are not new to Indonesia's multicultural society. Such marriages take place in the midst of society (in various social dimensions) and have been going on for a long time. However, that does not mean that the issue of Country marriage is not a problem, in fact it tends to always generate controversy in the community. There is an assumption that the cause is the existence of Law no. 1 of 1974 which does not accommodate the problem of Country marriage, because the mixed marriage referred to in Article 57 of the UUP is a marriage between two people who are subject to different laws, due to differences in nationality, not due to differences in religion.The purpose of writing this thesis is to be able to know, understand and analyze thoroughly or in depth about Country marriage according to Islamic Law, Civil Law and laws and regulations in Indonesia, and also want to know the factors of Country marriage and the problems or problems that arise due to Country marriage. The method used in this research is qualitative. This data collection technique is carried out using literature review, namely by collecting data and looking for ideas, theories, opinions, or findings that are closely related to the subject matter. The results showed that based on the Al-Quran letter Al-Baqoroh: 221, Law No. 1 of 1974 Article 2 paragraph (1), KHI, Articles 4, 40 and 44 all prohibit Country marriages. Because it is not in accordance with the purpose of marriage, namely to achieve a happy and eternal family based on the almighty God, Meanwhile, Marriage in the Civil Code / Burgerlijk Wetboek Article 26 is stated in article 26 BW